2018
DOI: 10.1155/2018/2760918
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Genes and Pathways in Triple-Negative Breast Cancer by Integrated Bioinformatics Analysis

Abstract: Purpose Triple-negative breast cancer refers to breast cancer that does not express estrogen receptor (ER), progesterone receptor (PR), or human epidermal growth factor receptor 2 (Her2). This study aimed to identify the key pathways and genes and find the potential initiation and progression mechanism of triple-negative breast cancer (TNBC). Methods We downloaded the gene expression profiles of GSE76275 from Gene Expression Omnibus (GEO) datasets. This microarray Super-Series sets are composed of gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 46 publications
(42 reference statements)
1
37
0
1
Order By: Relevance
“…TNBC-related studies have shown that these important GO aspects involved sister chromatid segregation, channel activity, passive transmembrane transporter activity, receptor regulator activity, extracellular matrix structural constituent and other aspects, and the results are consistent with the findings of previous TNBC-related studies. 4,54,55 Some new findings of our bioinformatics method require further study via experimental validation. Or analytical results showed that the influence of dysregulated mRNAs in the biological processes, cellular components, molecular functions and pathways may play pivotal roles in the pathogenesis of TNBC, all of which have been well documented.…”
Section: Discussionmentioning
confidence: 99%
“…TNBC-related studies have shown that these important GO aspects involved sister chromatid segregation, channel activity, passive transmembrane transporter activity, receptor regulator activity, extracellular matrix structural constituent and other aspects, and the results are consistent with the findings of previous TNBC-related studies. 4,54,55 Some new findings of our bioinformatics method require further study via experimental validation. Or analytical results showed that the influence of dysregulated mRNAs in the biological processes, cellular components, molecular functions and pathways may play pivotal roles in the pathogenesis of TNBC, all of which have been well documented.…”
Section: Discussionmentioning
confidence: 99%
“…Tian et al [21]only used coexpression analysis of lncRNAs with mRNAs to identify lncRNAs in TNBC. Dong et al [22] identi ed the essential genes and pathways related to TNBC by DEGs and Protein-Protein Interaction (PPI) networks. These correlation network analyses only indicate whether multiple genes are related to each other.…”
Section: Discussionmentioning
confidence: 99%
“…The five-year survival rate is still less than 10% [4][5][6]. Plenty of studies have been conducted to identify the underlying pathogenesis mechanisms, however, it's still not been illuminated [7][8][9]. In particular, there are few related studies on the expression modules of GBM, which has brought certain difficulties to the identification of key genes in the occurrence and recurrence of disease.…”
Section: Introductionmentioning
confidence: 99%